Inflammation-related mRNA gene expression absolute levels are associated with treatment-resistant depression in the BIODEP study. (September 2021) - Sforzini, Luca; Cattaneo, Annamaria; Ferrari, Clarissa; Turner, Lorinda; Mariani, Nicole; Enache, Daniela; Hastings, Caitlin; Lombardo, Giulia; McLaughlin, Anna P.; Nettis, Maria A.; Nikkheslat, Naghmeh; Worrell, Courtney; et al.
Abstract : Relative mRNA inflammation-related gene expression is increased in treatment-resistant depression (TRD). Here, we aim to investigate the absolute mRNA expression of two pro-inflammatory genes, interleukin (IL)1β and P2X7 receptor (P2RX7). Absolute mRNA quantitation does not require normalization with housekeeping genes but utilizes standard curves to provide a reliable absolute number of molecules. We examined 60 individuals with depression (20 TRD, 20 treatment-responsive, and 20 untreated) and 20 controls from the BIODEP study, using whole-blood mRNA qPCR to measure absolute gene expression. In the entire sample, we confirmed a positive correlation between absolute IL1β and P2RX7 mRNA values and standard values ( relative quantitation) (r=0.29, p=0.011 and r=0.22, p=0.05, respectively). In TRD individuals, we demonstrated statistically significant higher IL1β levels (+4.4%; mean±SEM = 7.63±0.07) compared with controls (7.31±0.09) ( t =2.70, p=0.010). We also identified a statistical trend towards higher P2RX7 levels in TRD (+5.2%; 3.45±0.07) compared with controls (3.28±0.06) ( t =1.79, p=0.08). Absolute gene expression is a valuable instrument to recognize the specific pro-inflammatory gene-expression signature associated with TRD.